2013
DOI: 10.1002/jbmr.1919
|View full text |Cite
|
Sign up to set email alerts
|

Fast Trabecular Bone Strength Predictions of HR-pQCT and Individual Trabeculae Segmentation–Based Plate and Rod Finite Element Model Discriminate Postmenopausal Vertebral Fractures

Abstract: While high-resolution peripheral quantitative computed tomography (HR-pQCT) has advanced clinical assessment of trabecular bone microstructure, nonlinear microstructural finite element (μFE) prediction of yield strength by HR-pQCT voxel model is impractical for clinical use due to its prohibitively high computational costs. The goal of this study was to develop an efficient HR-pQCT-based plate and rod (PR) modeling technique to fill the unmet clinical need for fast bone strength estimation. By using individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 65 publications
(168 reference statements)
2
33
0
Order By: Relevance
“…This idealized study provided fundamental assessment of PR μFE models in predicting mechanical properties of trabecular bone, independent of biological variations among human bone specimens and image noises existing in the imaging process. We have also applied PR μFE models on clinical HRpQCT images and demonstrated the ability of HRpQCT-based μFE PR models to predict bone strength and discriminate postmenopausal women with and without vertebral fractures [20]. Elastic modulus and yield strength predicted by HRpQCT-based PR models were strongly correlated with those by voxel models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This idealized study provided fundamental assessment of PR μFE models in predicting mechanical properties of trabecular bone, independent of biological variations among human bone specimens and image noises existing in the imaging process. We have also applied PR μFE models on clinical HRpQCT images and demonstrated the ability of HRpQCT-based μFE PR models to predict bone strength and discriminate postmenopausal women with and without vertebral fractures [20]. Elastic modulus and yield strength predicted by HRpQCT-based PR models were strongly correlated with those by voxel models.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we examined the accuracy and efficiency of the PR modeling strategy in an idealized, synthetic trabecular bone structure model, and demonstrated that the Young's modulus that was predicted by the ITS-based PR model correlated strongly with those by the voxel-based model at various voxel sizes [19]. Additionally, conversion from the voxel model to the PR model resulted in a 47-fold reduction in the number of elements [20]. Independently, Vanderoost et al developed specimen-specific skeleton based beam-shell μFE models for simulating trabecular bone elastic modulus [36].…”
Section: Introductionmentioning
confidence: 99%
“…These associations are not surprising because vertebral deformities are manifestations of mechanical impairment of the cortical and trabecular network. A recent study by Liu et al also reported that trabecular bone measures derived from distal extremities using HR-pQCT-based finite element analysis discriminate postmenopausal women with and without prevalent vertebral fractures [53]. …”
Section: Resultsmentioning
confidence: 99%
“…Next, we will briefly outline several representative studies modelling strength, damage, fracture and softening mechanisms of a single trabecula and trabecular bone. Different approaches have been employed including elastic-plastic constitutive laws and progressive damage evolution by element deletion [187][188][189][190][191][192][193][194][195][196][197][198][199][200][201]. Due to the complex architecture of trabecular bone, many of the models used micro-computed tomography (mCT) based three-dimensional voxel FEM models, which give an accurate representation of trabecular bone geometry [192][193][194][195].…”
Section: Models At the Microscale And Larger Scalesmentioning
confidence: 99%